Human Rights Protection in the Ecosystem of Surveillance Technology and Big Data Law Enforcement - Safrin Salam; Asmah; Muhammad Ramadan Kiro; Sulastri Yasim; Ibrahim Kayode Muhammed (Indonesia Media Law Review, 2026)
The rapid integration of surveillance technology and big data analytics into law enforcement has transformed contemporary governance, generating both security benefits and serious human rights concerns. This article examines how existing regulatory frameworks inadequately address the dynamic risks embedded in surveillance ecosystems and proposes a lifecycle-based governance response. Using a qualitative normative-empirical methodology, the study combines doctrinal legal analysis of international human rights law with comparative regulatory assessment and interdisciplinary technology governance theory. The findings reveal structural fragmentation, insufficient algorithmic transparency, weak proportionality assessment, and reactive oversight mechanisms that fail to capture risks across data collection, storage, analysis, sharing, and deletion. In response, the study develops a Dynamic Human Rights Risk Assessment Model that operationalizes proportionality, necessity, transparency, and accountability at each stage of the surveillance data lifecycle. The model embeds continuous monitoring, mandatory impact assessments, and independent oversight within surveillance infrastructures, shifting governance from static compliance to adaptive human rights stewardship. The research concludes that lifecycle-based regulation provides a coherent and flexible framework capable of safeguarding fundamental rights while accommodating technological innovation in complex surveillance environments.